Safe and easy method with little modification in technique is useful for successful internal jugular vein cannulation on the same side even after intra-arterial puncture without using ultrasound guidance in adult cardiac patients - Rajesh Thosani; Jigar Patel; Hemang Gandhi; Chirag Doshi; Jignesh Kothari (Annals of Cardiac Anaesthesia, 2016)
Background: The modification in technique is useful for successful right-sided internal jugular vein (IJV) cannulation on the same side even after intra-arterial puncture without using ultrasound guidance in adult patients. Materials and Methods: This study was carried out in total 160 adult patient from American Society of Anesthesiologists Grade II to III patients male (n = 95) and female (n = 65) who underwent cardiac surgery where cannulation was done on right sided by triple lumen catheter (7 French) using Seldinger technique. Results: Majority of patients were cannulated successfully by Seldinger technique with single or double attempt except for five patients in which arterial puncture occurred. All five patients were cannulated successfully on the same side with this modified technique without any significant major complications. They were managed by application of blocker at the end of arterial needle puncture without removing it. In our routine practice, we were used to removing this needle and applying compression for few minutes to prevent hematoma formation after an arterial puncture. In this study, cannula was used as a marker or guideline for the relocation of IJV on the same side and recannulation was performed by changing the direction of needle on same side lateral to the previous one and without going towards the same direction to prevent the arterial puncture again. Conclusion: Most simple and useful modified technique for institutes where the complications are most common with trainee doctors and in hospitals where there is no advanced facility like ultrasound-guided cannulation available. By this modification, it will be time saving, very comfortable, and user-friendly technique with high success rate.